In-Patient Code Stroke: A Quality Improvement Strategy to Overcome Knowledge-to-Action Gaps in Response Time. Issue 8 (August 2017) - Kassardjian, Charles D.; Willems, Jacqueline D.; Skrabka, Krystyna; Nisenbaum, Rosane; Barnaby, Judith; Kostyrko, Pawel; Selchen, Daniel; Saposnik, Gustavo
Abstract : Background and Purpose—: Stroke is a relatively common and challenging condition in hospitalized patients. Previous studies have shown delays in recognition and assessment of inpatient strokes leading to poor outcomes. The goal of this quality improvement initiative was to evaluate an in-hospital code stroke algorithm and educational program aimed at reducing the response times for inpatient stroke. Methods—: An inpatient code stroke algorithm was developed, and an educational intervention was implemented over 5 months. Data were recorded and compared between the 36-month period before and the 15-month period after the intervention was implemented. Outcome measures included time from last seen normal to initial assessment and from last seen normal to brain imaging. Results—: During the study period, there were 218 inpatient strokes (131 before the intervention and 87 after the intervention). Inpatient strokes were more common on cardiovascular wards (45% of cases) and occurred mainly during the perioperative period (60% of cases). After implementation of an inpatient code stroke intervention and educational initiative, there were consistent reductions in all timed outcome measures (median time to initial assessment fell from 600 [109–1460] to 160 [35–630] minutes and time to computed tomographic scan fell from 925 [213–1965] to 348.5 [128–1587] minutes). Conclusions—: Our study reveals the efficacy of an inpatient code stroke algorithm and educational intervention directed at nurses and allied health personnel to optimize the prompt management of inpatient strokes. Prompt assessment may lead to faster stroke interventions, which are associated with better outcomes. Abstract : Supplemental Digital Content is available in the text.